2004
DOI: 10.1007/s10350-004-0645-5
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of the Ileal Pouch in Patients Developing Crohn's Disease

Abstract: Patients who undergo ileal pouch-anal anastomosis and are subsequently found to have Crohn's disease experience significant morbidity. Preoperative characteristics, including the presence of anal disease, were not predictive of subsequent pouch failure. We choose not to recommend the routine application of ileal pouch-anal anastomosis in any subset of patients with known Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 20 publications
2
75
0
6
Order By: Relevance
“…Thus, the most pertinent question regarding the surgical decisions in indeterminate inflammatory bowel disease patients is whether to provide an ileal pouch-anal anastomosis for continence restoration. Ileal pouch-anal anastomosis is most clearly indicated for ulcerative colitis patients, but remains [17][18][19] Based on long-term clinical outcome studies, it appears that most indeterminate inflammatory bowel disease patients will ultimately behave clinically like ulcerative colitis patients. 20,21 Accordingly, indeterminate inflammatory bowel disease patients are often deemed appropriate candidates for ileal pouch-anal anastomosis, although they have an increased complication rate compared with ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the most pertinent question regarding the surgical decisions in indeterminate inflammatory bowel disease patients is whether to provide an ileal pouch-anal anastomosis for continence restoration. Ileal pouch-anal anastomosis is most clearly indicated for ulcerative colitis patients, but remains [17][18][19] Based on long-term clinical outcome studies, it appears that most indeterminate inflammatory bowel disease patients will ultimately behave clinically like ulcerative colitis patients. 20,21 Accordingly, indeterminate inflammatory bowel disease patients are often deemed appropriate candidates for ileal pouch-anal anastomosis, although they have an increased complication rate compared with ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24]43,44 Some studies show an acceptable low rate of complications, morbidity, and pouch failure, [22][23][24] whereas others have shown poor results. 43,44 In general, pouch complications and failure rates range from 35 to 90%.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24]43,44 Some studies show an acceptable low rate of complications, morbidity, and pouch failure, [22][23][24] whereas others have shown poor results. 43,44 In general, pouch complications and failure rates range from 35 to 90%. [22][23][24]43,44 Although some studies have shown better outcome for patients with Crohn's colitis without perianal disease or small bowel involvement, 23 other studies have not found any clinical or pathological features predictive of outcome after an ileal pouch-anal anastomosis procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of granulomas is conclusive, 41 many studies have also included 'minor' pathologic criteria such as transmural inflammation, discontinuous disease, and fissuring ulcers in the surgical specimen to establish the diagnosis of CD immediately after colectomy. 7,9,12,15,16,34,39,[42][43][44][45][46][47] We consider patients with these minor criteria to have IC and not CD since these features can not only be observed in fulminant UC but may also reflect treatment effect. Furthermore, we found no significant difference in clinical outcome (i.e., CD development) after IPAA between the UC, IBD-U, and IC patient subgroups.…”
Section: Discussionmentioning
confidence: 99%